PENYEMPROTAN DESINFEKTAN SEBAGAI TINDAKAN PREVENTIF TERHADAP PENULARAN VIRUS CODID-19 DI DUSUN GENTING, CEPOGO-BOYOLALI - LENI KRISNAWATI; ALEAN KISTIANI H.S (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
One of the efforts to keep the environment clean, healthy, and free from exposure to the corona virus is by spraying disinfectant liquid. The government always urges people to make disinfectants independently at home. However, many people in Genting Rt.07 Rw.02 Genting Village, Cepogo District, Boyolali Regency still do not know how to make disinfectants, even if people know how to make disinfectants in general they just mix chemicals without knowing the content of the compounds in them. in packaging bottles, what are the properties of these compounds and what is the exact dosage. As a result, mixing these chemicals can actually have a negative impact on them, such as the formation of new compounds that are harmful to their health. Therefore, activities in the form of education about making disinfectants are very necessary.